ShadowOui: a new visual environment for X‐ray optics and synchrotron beamline simulations. (14th October 2016) - Rebuffi, Luca; Sánchez del Río, Manuel
Abstract : ShadowOui is introduced, a new computer environment for X‐ray optics, beamline simulations and virtual experiments using the ray‐tracing code SHADOW . Abstract : A new computer environment to perform simulations on synchrotron experiments has been designed. It performs ray‐tracing simulations using the popular ray‐tracing code SHADOW . With this new application one can define, in a very easy and elegant way, one or several optical systems (beamlines) and perform calculations of the propagation of the X‐ray beam through it. Many complementary tools and supplementary calculations improve and extend the functionality of SHADOW to deal with complex optical system optimization, including compound optical elements, iterative calculations, some sample simulations, and implementing corrections for wave optics via a hybrid model.